2014
DOI: 10.7482/0003-9438-57-024
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to assess the welfare of horses maintained in herd systems

Abstract: The aim of the study was to assess the welfare, using the Welfare Quality criteria, of horses maintained in natural conditions. The study material was a herd of Hucul horses, consisting of 14 mares with offsprings and a stallion, maintained in a herd system on pastures. The research was conducted in the months of March, July and November in 2010 and 2012. Nutrition assessment was based on access to feedstuff, water, including their state. Analysis of levels of maintenance involved evaluating prevailing weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It was shown that horses living in long-term individual boxes experienced an improvement in their mental state through a positive cognitive bias when they were released in pasture with congeners [78], likely indicating a better overall welfare state. The absence of stereotypies in pasture was also already mentioned [79]. However, the relationship between stereotypies and welfare remains unclear, and they should not be used as the only behavioural indicators to assess the welfare state [15].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that horses living in long-term individual boxes experienced an improvement in their mental state through a positive cognitive bias when they were released in pasture with congeners [78], likely indicating a better overall welfare state. The absence of stereotypies in pasture was also already mentioned [79]. However, the relationship between stereotypies and welfare remains unclear, and they should not be used as the only behavioural indicators to assess the welfare state [15].…”
Section: Discussionmentioning
confidence: 99%
“…Research about the welfare of livestock has been mainly conducted to intensively farmed animals with or without access to pastures (Turner and Dwyer, 2007;Charlton and Rutter, 2017;Carcangiu et al, 2018) and to certain regions (Mikuš et al, 2018). For this reason, information concerning the welfare of grazing ruminants is quite restricted (Bojkovski et al, 2014;Topczewska, 2014;Antkowiak et al, 2012;Karasabbidis et al, 2014;Gilhaus and Hölzel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors observed fewer behavioral disorders in horses living in paddocks or on pasture [ 4 , 11 , 12 , 13 , 14 ], although in stallions, this housing system may favor fights which can cause severe lesions and even the death of the animals in some cases [ 3 , 4 ]. More recently, Gehlen et al [ 5 ] concluded, based on an extended literature review, that group-housing of stallions represents the most adequate system if a few characteristics regarding the exercise area (size and design), the composition of the group, and the horses are considered.…”
Section: Introductionmentioning
confidence: 99%